Work Integrated Learning Program of Bachelor of Science in Business Administration Major in Human Resource Development Management - Concepcion, Joanne S. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to examine the processes of Work Integrated Learning, the level of abilities and qualities of student-trainees, the strengths and weaknesses of communicating with others the problems experienced in their internship, and the recommendations of Practicum Supervisors to enhance student-trainee results further. The study used descriptive analysis and evaluated the data obtained by frequency, percentage, rank, and weighted average. This research concluded that the Work Integrated Learning program maintained an excellent procedure in the internship conduct. It also reflects that the coordinators’ business visits are limited because they have other subject loads and assignments during the semester. In terms of their abilities and qualities, student trainees meet the standards of co-operating organizations. Supervisors regarded the sense of duty, well dressed, very polite, and the ability to quickly grasp a given assignment as student-trainee strengths. Low trust to communicate their ideas and logically, fluency in using the English language, writing business correspondence, finding an internship location, and time management are the common problems students face. Through training courses and workshops, Practicum Supervisors suggest developing soft skills to prepare the students in their internship to directly develop their business writing skills, time management, and self-confidence.